PERBANDINGAN ENTERAL DAN PARENTERAL NUTRISI PADA PASIEN KRITIS : A LITERATURE REVIEW - Setianingsih -; Anastasia Anna (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Almost all critically ill patients undergo an incapable to eat because of the reduced level ofconsciousness, sedation giving, intubated and malnutrition. The disturbance of nutrition will influence the immunity system, infection risk, mortality, healing process, length of ICU stay, andlength of mechanical ventilation. The precise nutrition given with enteral nutrition (EN) and parenteral nutrition (PN) will determine the full filment dose of nutrition according to thepatient’ needs. This Literature Review aimed to give the appropriate summary and development the method of enteral and parenteral nutrition given to critically ill patients in ICU. Theresearch conducted by doing reviews on the results of research published from year 2009 until 2013 obtained from several journal database such as CINAHL, EBSCO, Proquest and Google Scholar. The data searching done by using these key words, among them were enteral nutrition,parenteral nutrition, ICU, critically ill patients. The concept obtained refered to the given ofenteral nutrition, parenteral nutrition, the advantages and disadvantages of EN and PN,complication happened during the given of EN and PN, also the appropriate method forcritically ill patients surgery and medical. In critically ill patients, EN has always been the firstchoice and PN into alternative method. The supportive nutrition is very important in thetreatment of critically ill patient that can be given enterally, parenterally, or both of them canbe used together. Thus, the given of nutrition need to be conducted as a focus of nursing studyin the area of critical care nursing.Keyword: enteral nutrition, parenteral nutrition, ICU, critically ill patients